Pilipino and English word associations by Pilipino-English bilinguals - Tiglao, Aurelia D.; Capco, Clemencia S. ([Metro Manila] Psychological Association of the Philippines, 1971)
This report presents primary and secondary responses to each of the first 50 Kent-Rosanoff stimulus words. Pilipino and English responses were collected from samples of pupils attending kindergarten and grades 3,6 and 10 to study developmental changes in the word association responses of Pilipino-English bilinguals.
Includes bibliographical references (pages 42-43)
Keywords: Psychology Philippines -- Periodicals